Recent Advances in Neodymium as a Magnetic Nanoparticle Material Candidate for Microwave Absorption - Dea Dwi Ananda; Thessa Octavia Joyetta Tarigan; Tiara Rizki Yulita; Kayla Sophia Putri; Hazzha Azzahra; Sultan Napoleon; Mayang Fauziah Putri Kuntjahjono; Almanda Naura Candra Putri; Muhammad Afif Aji Patria; Yusuf Bramastya Apriliyanto; Rahmat Basuki; Nugroho Adi Sasongko; Akhmad Rifai; Nuha Nuha (Indonesian Scholar Society, 2026)
Magnets are materials that can attract or repel other objects due to the magnetic field generated by the arrangement of electron spin moments in atoms. One important magnetic material is magnetite (Fe₃O₄), which has been widely used and continues to be developed to meet the needs of modern technology. Innovation in material development is achieved through ion-substitution strategies, such as the use of the trivalent metal neodymium to replace Fe³⁺ in the ferrite structure. This strategy allows regulation of the microstructure and ion distribution in the crystal lattice, thereby significantly influencing the material's magnetic performance. Neodymium nanoparticles are known to exhibit superparamagnetic properties due to their tiny dimensions, so that each particle behaves as a single magnetic domain. These particles possess significant magnetic moments; however, their magnetization disappears once the external magnetic field is removed due to thermal fluctuations. The magnetic behavior of neodymium-based nanoparticles is strongly influenced by particle size, crystal structure, composition, and synthesis conditions. Based on theoretical calculations, neodymium exhibits a high magnetic moment due to its unpaired 4f electrons and strong spin–orbit coupling, with a magnetic spin moment of approximately 2.85 × 10⁻²² JT⁻¹. The characteristics of 4f electrons that are localized and protected by the outer shell produce strong spin-orbit coupling, contributing to a significant total magnetic moment and high crystal magnetic anisotropy. This phenomenon strongly aligns the magnetization along specific crystallographic directions, thereby stabilizing the magnetic orientation. This unique property makes neodymium a potential candidate for high-performance magnetic materials, including in high-frequency electromagnetic wave absorption technology. Nd-based magnetic materials exhibit enhanced microwave absorption performance through improved dielectric/magnetic losses and impedance matching, achieving reflection loss values below −40 dB with broad absorption bandwidths for electromagnetic shielding and radar absorbing applications.